Hedging Local Products : Optimizing The Processed Products of Sago Commodity to Become More Competitive Globally Study Case Riau Province - Cifebrima Suyastri (Journal of Diplomacy and International Studies, 2018)
This study aimed to analyze the strategy of increasing food security and self-reliance through the Riau province of processed products sago as a substitute for food diversification . By leveraging the leading sectors in the region , it is expected to be a major driving force in improving both regional and national economy, as well export competitiveness in the global market. This paper getting its samples by gathering data from questionnaires conducted on SMEs and sago industry in the islands of Meranti. It also apply the SWOT analysis and measurement of product competitiveness through diamond porter to determine the potential of the processed products of sago. Moreover , to strengthen the sharpness of analysis, such direct observation in the form of unstructured interviews and gather relevant literature will be performed. The authors find new strategies in providing solutions to improve food security and self-reliance through the optimization of processed products of sago . Meeting the needs of the region in the consumption of basic materials requires another alternative to avoid product shortages and increase the potential of the region in developing the seed sector. The result is the increase of processed products of sago and to make it a superior product that can compete in national and global markets.